MicroRNA miR396 Regulates the Switch between Stem Cells and Transit-Amplifying Cells in Arabidopsis Roots. Issue 12 (8th December 2015) - Rodriguez, Ramiro E.; Ercoli, María Florencia; Debernardi, Juan Manuel; Breakfield, Natalie W.; Mecchia, Martin A.; Sabatini, Martin; Cools, Toon; De Veylder, Lieven; Benfey, Philip N.; Palatnik, Javier F.
Abstract : Regulatory interactions between microRNA miR396 and PLT and GRF transcription factors affect the boundary between root stem cells and the rapidly dividing transit-amplifying cells. Abstract: To ensure an adequate organ mass, the daughters of stem cells progress through a transit-amplifying phase displaying rapid cell division cycles before differentiating. Here, we show that Arabidopsis   thaliana microRNA miR396 regulates the transition of root stem cells into transit-amplifying cells by interacting with GROWTH-REGULATING FACTORs ( GRFs ). The GRFs are expressed in transit-amplifying cells but are excluded from the stem cells through inhibition by miR396. Inactivation of the GRFs increases the meristem size and induces periclinal formative divisions in transit-amplifying cells. The GRFs repress PLETHORA ( PLT ) genes, regulating their spatial expression gradient. Conversely, PLT activates MIR396 in the stem cells to repress the GRFs . We identified a pathway regulated by GRF transcription factors that represses stem cell-promoting genes in actively proliferating cells, which is essential for the progression of the cell cycle and the orientation of the cell division plane. If unchecked, the expression of the GRFs in the stem cell niche suppresses formative cell divisions and distorts the organization of the quiescent center. We propose that the interactions identified here between miR396 and GRF and PLT transcription factors are necessary to establish the boundary between the stem cell niche and the transit-amplifying region.